Neue Winderosionsgefahr im Weizenanbaugebiet der Great Plains - Ahnert, Frank (ERDKUNDE, 1955)
The wheat areas of the Great Plains' States have suffered from drought seven times during the past hundred years. The last of these droughts occurred during the nineteen-thirties. A more humid period of climate and the introduction of soil conservation measures resulted in a recovery of wheat cultivation during the nineteen-forties. Since the summer of 1952 precipitation has again fallen far below the normal amount; several new records of duration of droughts were established, and the relationship between the area sown and the area harvested, as well as yields per acre have again deteriorated. In spring 1953 the first serious damage by wind erosion occurred, and during the winter of 1954-55 4 million acres suffered from soil erosion by wind. Altogether 20 million acres are now ready to blow and it is to be feared that the agriculture of the Great Plains will suffer particularly heavy damage this year.